TiO2/CdS/CdSe quantum dots co-sensitized solar cell with the staggered-gap (type-II) heterojunctions for the enhanced photovoltaic performance. Issue 6 (15th March 2023) - Monika, S.; Mahalakshmi, M.; Pandian, M. Senthil
Abstract: The effect of co-sensitization and ZnS passivation on the photovoltaic performance of CdS quantum dot sensitized solar cells (QDSSCs) were investigated. The deposition of CdS, CdSe quantum dots (QD) and ZnS passivation on TiO2 photoanode was carried out by successive ionic layer adsorption and reaction (SILAR) method. CdS/CdSe co-sensitization developed two staggered type-II heterojunctions at TiO2 /CdS and CdS/CdSe interfaces and resulted a cascade energy band structure. This suitable band alignment facilitated the double charge transfer mechanism at each heterojunction and transported the electrons easily into the photoanode. The narrow bandgap sensitizers CdS and CdSe significantly improved the potential utilization of solar spectrum with more charge carrier generation. ZnS passivation on QD surface suppressed electrode/electrolyte interfacial charge recombination and facilitated more electron injection from QDs into TiO2 photoanode. The EDAX elemental mapping results inferred that CdS, CdSe and ZnS have efficiently covered the TiO2 surface. TiO2 /CdS and CdS/CdSe interfaces and the amorphous nature of ZnS could be verified with HRTEM images. Hence, the co-sensitization and surface passivation played a significant role to enhance the PCE of CdS QDSSC from 1.9% to 4.05%. Highlights: Co-sensitization of CdS/CdSe quantum dots on TiO2 photoanode resulted a cascade band alignment. The staggered type-II heterojunctions have facilitated faster charge transport through double charge transfer mechanism. Co-sensitization has widened the light absorption range with more charge carrier generation and increased current density. ZnS passivation layer suppressed the recombination by passivating the defect sites on quantum dot surface. Co-sensitization and surface passivation enhanced the PCE of CdS QDSSC from 1.9% to 4.05%.